The Translation Shift in The Translation of The English Recount Text Into Indonesian at SMP Swasta Ben’s Group Buntu Bayu Hatonduhan - Manurung, Novita Gresiana; Siahaan, Sanggam; Purba, Christian Neni (Innovative: Journal Of Social Science Research, 2024)
This research was intended to find out types of translation shift in category shift according to J.Catford  of students in translating recount text from English into Indonesia at SMP Swasta Ben's Group Buntu Bayu Hatonduhan. Therefore, the researcher formulated a question as the problem. As follows: “What are the translation shift used in translating recount text from English into Indonesian?" The researcher was used qualitative design. The researcher used grade eight students of SMP Swasta Ben's Group Buntu Bayu Hatonduhan as the population and used 25 students as the sample. The instrument of the research of this research was test recount text. The data were collected by analyzed the result of students’ translation and correction. The research finding showed that students were types of translation shift in translating recount text from English into Indonesia. From the results of students' translations in the first recount text, it was found that the highest number of types of translation shifts found in the results of students' translations was unit shifts of 135 data from 25 students. The second highest types of translation shifts were structure shifts of 75 data from 25 students. And the third highest was class shifts of 62 data from 25 students, and the last was intra-system shifts of 28 data from 25 students. Then from the results of students' translations in the second recount text, the first highest was class shifts of 153 data from 25 students, the second highest was structure shifts of 67 data from 25 students, the third highest was unit shifts of 55 data from 25 students, and the last was intra-system shifts of 26 data from 25 students. It can be concluded from both recount texts translated by students from English to Indonesian, that all contained types of translation shifts (category shifts), namely structure shifts, class shifts, unit shifts, and intra-system shifts.